Evaluation of scoring models for identifying the need for therapeutic intervention of upper gastrointestinal bleeding: A new prediction score model for Japanese patients. Issue 7 (3rd May 2016) - Iino, Chikara; Mikami, Tatsuya; Igarashi, Takasato; Aihara, Tomoyuki; Ishii, Kentaro; Sakamoto, Jyuichi; Tono, Hiroshi; Fukuda, Shinsaku
Abstract : Background and Aim: Multiple scoring systems have been developed to predict outcomes in patients with upper gastrointestinal bleeding. We determined how well these and a newly established scoring model predict the need for therapeutic intervention, excluding transfusion, in Japanese patients with upper gastrointestinal bleeding. Methods: We reviewed data from 212 consecutive patients with upper gastrointestinal bleeding. Patients requiring endoscopic intervention, operation, or interventional radiology were allocated to the therapeutic intervention group. Firstly, we compared areas under the curve for the Glasgow‐Blatchford, Clinical Rockall, and AIMS65 scores. Secondly, the scores and factors likely associated with upper gastrointestinal bleeding were analyzed with a logistic regression analysis to form a new scoring model. Thirdly, the new model and the existing model were investigated to evaluate their usefulness. Results: Therapeutic intervention was required in 109 patients (51.4%). The Glasgow‐Blatchford score was superior to both the Clinical Rockall and AIMS65 scores for predicting therapeutic intervention need (area under the curve, 0.75 [95% confidence interval, 0.69–0.81] vs 0.53 [0.46–0.61] and 0.52 [0.44–0.60], respectively). Multivariate logistic regression analysis retained seven significant predictors in the model: systolic blood pressure <100 mmHg, syncope, hematemesis, hemoglobin <10 g/dL, blood urea nitrogen ≥22.4 mg/dL, estimated glomerular filtration rate ≤ 60 mL/min per 1.73 m 2, and antiplatelet medication. Based on these variables, we established a new scoring model with superior discrimination to those of existing scoring systems (area under the curve, 0.85 [0.80–0.90]). Conclusion: We developed a superior scoring model for identifying therapeutic intervention need in Japanese patients with upper gastrointestinal bleeding.